2013
DOI: 10.1017/s0007114513003917
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal analysis of dietary patterns in Chinese adults from 1991 to 2009

Abstract: Our aims were to identify the changes or stability in the structure of dietary patterns and the tracking, trends and factors related to the adherence of these patterns in China from 1991 to 2009. We used seven waves of the China Health and Nutrition Survey and included 9,253 adults with ≥3 waves complete. Diet was measured over a 3-day period with 24-hr recalls and a household food inventory. Using factor analysis in each wave we found that the structure of the two dietary patterns identified, remained stable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
148
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 164 publications
(166 citation statements)
references
References 36 publications
(33 reference statements)
16
148
0
2
Order By: Relevance
“…We previously found a similar dietary pattern in this population that we call “modern high-wheat.”. (21) The second factor from the PCA, which we call “traditional southern,” was positively related to intake of rice, high-fat pork, organ meats, poultry and game, and fish and seafood and inversely associated with intake of wheat flour, wheat buns and breads, and corn and coarse grains. The factor loadings from the RRR seemed to be close to the modern high-wheat dietary pattern (PCA 1) and the opposite of the traditional southern (PCA 2) at the same time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously found a similar dietary pattern in this population that we call “modern high-wheat.”. (21) The second factor from the PCA, which we call “traditional southern,” was positively related to intake of rice, high-fat pork, organ meats, poultry and game, and fish and seafood and inversely associated with intake of wheat flour, wheat buns and breads, and corn and coarse grains. The factor loadings from the RRR seemed to be close to the modern high-wheat dietary pattern (PCA 1) and the opposite of the traditional southern (PCA 2) at the same time.…”
Section: Resultsmentioning
confidence: 99%
“…(23, 24) To estimate the residuals, we ran several logistic regressions with each binary food group as the dependent variable and geographic region, urbanicity index, education, and income as the independent variables. Our variable selection for the estimation of residuals is based in previous work, (21) where we found that in this population these variables were the most influential on dietary patterns. We used these residuals (difference between the observed and the predicted probability) as intake variables on the RRR procedure.…”
Section: Methodsmentioning
confidence: 99%
“…Data were recorded by trained interviewers through face-to-face interviews, and include the types, amounts, types of meals (breakfast, lunch, dinner, snack) and locations (home, school or the workplace, restaurant or food stand, relative’s or friend’s house, nursery school, festival or celebration) of consumption of all food items consumed[33]. …”
Section: Methodsmentioning
confidence: 99%
“…16 After removing food groups with less than 5% consumers overall, to accommodate a high proportion of non-consumers for several food groups and to allow for consistent comparisons across groups, each of the 34 food and condiment groups was categorized as a binary variable (consumer/nonconsumer for food groups with less than 50% of consumers; or above/below median for those with higher intakes) and included in PCA. 26 We derived dietary patterns based on the polychoric correlation matrix and orthogonal varimax rotation in STATA. On the basis of eigenvalue>1.0, scree plot (eFigure 1) and interpretability, 2 factors were retained (see eTable 2 for food examples and factor loading), which together accounted for 23% of the variance in intakes (12% and 11% for pattern 1 and 2 respectively).…”
Section: Methodsmentioning
confidence: 99%